2019
DOI: 10.1016/j.clnu.2018.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Intake of caffeine from all sources and reasons for use by college students

Abstract: As in the general U.S. population, coffee is the primary source of caffeine intake among the college students surveyed. Energy drinks provide less than half of total daily caffeine intake but more than among the general population. Students, especially women, consume somewhat more caffeine than the general population of individuals aged 19-30 y but less than individuals aged 31-50 y.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
126
6
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(166 citation statements)
references
References 42 publications
(49 reference statements)
24
126
6
10
Order By: Relevance
“…Caffeine is the most commonly used psychostimulant worldwide and mainly consumed in forms of coffee, tea, energy drink, and soda [1][2][3][4] . Although caffeine is mostly considered to be non-addictive, the observed physical and psychological dependence 5,6 consolidate its regular consumption [7][8][9] through the caffeineinduced reinforcing effects 10 , as well as the motive to resist withdrawal symptoms 11 and to increase alertness 12 . Higher alertness after acute caffeine intake 13 mirrors a reduced homeostatic sleep pressure, which is also evident in a reduced depth of sleep 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Caffeine is the most commonly used psychostimulant worldwide and mainly consumed in forms of coffee, tea, energy drink, and soda [1][2][3][4] . Although caffeine is mostly considered to be non-addictive, the observed physical and psychological dependence 5,6 consolidate its regular consumption [7][8][9] through the caffeineinduced reinforcing effects 10 , as well as the motive to resist withdrawal symptoms 11 and to increase alertness 12 . Higher alertness after acute caffeine intake 13 mirrors a reduced homeostatic sleep pressure, which is also evident in a reduced depth of sleep 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies, carried out mainly with university students and other young populations [9,10,11], have reported that caffeine intake was higher in men, older people and in smokers [10,11]. However, the factors associated with the habit of coffee consumption have scarcely been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…9 Because it is a stimulant, caffeine can have positive effects on mood, especially alertness, as well as cognitive performance, in relatively low doses in single servings of many foods; and its widespread popularity likely reflects these positive behavioral properties. [10][11][12][13][14] However, as a consequence of these properties, caffeine, especially when consumed later in the day in high doses, can interfere with sleep. [15][16][17] Caffeine's effects are dose-dependent, and per capita daily intake by adults in the United States is about 186 mg/d and has been stable for 10 years and perhaps much longer.…”
mentioning
confidence: 99%